The use of the psychosemantic method of multiple identifications in the study of ethnic representations (the results of the survey in PFUR) - A V Medvedeva (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2014)
The article describes the peculiarities of the development and use of multiple identifications method and the results of an empirical study of the images of ethnic groups. The author considers the problem of reconstructing the semantic space, describes the instruments of the research based on the psychosemantic method of multiple identifications, analyzes the positions of different ethnic images in the subjective semantic space of PFUR students, identifies the possibilities and limitations of the method in sociological surveys.